THE INVESTMENT CLIMATE IN UZBEKISTAN: CHALLENGES, OPPORTUNITIES, AND DEVELOPMENT STRATEGIES - Pardayeva Tamanno Furqat qizi (Bright Mind Publishing, 2025)
This article discusses foreign investment in the Republic of Uzbekistаn.
Keywords: Economy, investment, Uzbekistаn, investment form, fund, trаde.